2007
DOI: 10.1016/j.placenta.2006.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin Expression in Human Trophoblasts from Early Placenta: Comparative Study Between Villous and Extravillous Trophoblastic Cells

Abstract: Human trophoblast differentiates into two pathways: extravillous cytotrophoblasts (EVCT) that invade the uterus wall and villous cytotrophoblasts (VCT) that fuse to form the syncytiotrophoblast (ST) involved in placental exchanges and endocrine function. It is established that hCG is produced and secreted by the ST into the maternal compartment where it plays a key endocrine role and stimulates ST formation in an autocrine manner. Herein, we investigated hCG expression in early placentas by immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 41 publications
(45 reference statements)
1
58
0
2
Order By: Relevance
“…The amount of hCG actually reflect the number of viable cytotrophoblast and syncytiotrophoblast cells producing the hormone [1,2]. Our results indicate that, at equivalent time intervals subsequent to fertilization, serum hCG concentrations are significantly higher in ongoing pregnancies achieved after slow-freezing embryo transfer compared with those after vitrified embryo transfer.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The amount of hCG actually reflect the number of viable cytotrophoblast and syncytiotrophoblast cells producing the hormone [1,2]. Our results indicate that, at equivalent time intervals subsequent to fertilization, serum hCG concentrations are significantly higher in ongoing pregnancies achieved after slow-freezing embryo transfer compared with those after vitrified embryo transfer.…”
Section: Discussionmentioning
confidence: 69%
“…A number of studies have reported that β-hCG level represents trophoblastic mass and function and is predictive of pregnancy outcomes [1,[3][4][5][6][7], yet early β-hCG values after frozen embryo transfers have not studied. We further evaluated whether vitrification of day 3 embryos have an effect on β-hCG level of early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations